Presidential Perspectives: Engaging a Region to Transform Its Future - Welty, John D. (Educational (Re)naissance, 2012)
On July 11, 2011, Fresno California was designated as one of the six initial communities for the Strong Cities, Strong Communities (SC2) initiative, a new and customized pilot project by the Obama administration to strengthen local capacity and spur economic growth in local communities. A team of federal administrators representing the Environmental Protection Agency (PA), the Economic Development Agency (EDA), the U.S. Department of Agriculture (USDA), the Department of Transportation (DOT), the U.S. Department of Housing and Urban Development (HUD), the Minority Business Development Agency (MBDA), the U.S. Department of Health and Human Services (HHS), and the U.S. Department of Labor (DOL) will work with local governments, the private sector, and other institutions to leverage federal dollars and support the work being done at the local level to encourage community development. Federal administrators will be on site and housed at Fresno City Hall. By integrating government investments and partnering with local communities, SC2 channels the resources of the federal government to help empower cities with established planning and strong leadership as they develop and implement their vision for economic growth. This designation culminates years of work by region leaders to align resources and build a network to transform a region.